Peer-Feedback Training Format: An Effective Writing Formative Assessment Tool - Luisa Josefa Corsi García (Voces y Silencios: Revista Latinoamericana de Educación, 2025)
This text presents a personal pedagogical reflection based on the experience I had in  a continuous teacher development plan I took part in for over a year, applying its results in eight different ESL courses at the intermediate levels of 5 and 6 of the Academic English Support Program at Universidad de Los Andes. The purpose of the Continuous Professional Development program, specifically in the working group described in this experience, was to enhance students’ writing skills through teachers’ instruction and using a Peer-feedback Training Format based on the principles of formative assessment, formative feedback and peer-feedback. First, I provide a general introduction and the teaching context. Second, I describe the writing teaching practice and the Peer feedback Training Format. Third, I present my pedagogical insights. Then, I draw my conclusions, and finally, I give some recommendations for future directions.